Extending the limits of reconstructive microsurgery in elderly patients. Issue 8 (August 2016) - Klein, H.J.; Fuchs, N.; Mehra, T.; Schweizer, R.; Giesen, T.; Calcagni, M.; Huber, G.F.; Giovanoli, P.; Plock, J.A.
Summary: Background: Population aging strongly affects the demographic development of industrialized countries. While microsurgical procedures were initially believed to be only feasible in patients of younger age because of the duration of the surgical procedure and the higher risk of vascular insufficiency due to age-related comorbidities, it has become evident that these procedures are beneficial even for patients at an advanced age. Methods: We retrospectively investigated microsurgical procedures in a patient cohort ( n = 25 with 27 free flaps) with a minimum age of 78 years with regard to patients' characteristics, flap survival, and postoperative surgical and medical complications. Results: Median age was 81 years (IQR 6). Most defects were located in the head and neck region. The mean operation time was 384 min (standard deviation (SD) 131). Flap failure was observed in three cases (11%). The median length of hospital stay was 17 days (interquartile range (IQR) 8). The mean ASA score was 2.48. Patients' age and ASA group did not correlate. The mortality rate was 4%. Postoperative surgical complications were observed in 11 cases (41%), while 19 patients (70%) showed one or more medical complications. Higher ASA classes tended to show more postoperative complications. However, neither age nor operating time nor ASA status showed significant influence on the occurrence of postoperative medical or surgical complications. Conclusion: There is growing demand for structural and functional restoration using free tissue transfer in an aging population. If there are no alternative treatment options available promising similar structural and functional preservation, free tissue transfer is justifiably in very old patients despite a potentially increased flap failure. As such, free tissue transfer is used as a curative treatment concept aiming at a maximum of patients' independence and early ambulation. Occurrence of complications can be diminished by adequate patient selection and thorough perioperative care.